2007
DOI: 10.1529/biophysj.107.110056
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Flanking Bases in HIV-1 RNA DIS Kissing Complexes Studied by Molecular Dynamics

Abstract: Explicit solvent molecular dynamics simulations (in total almost 800 ns including locally enhanced sampling runs) were applied with different ion conditions and with two force fields (AMBER and CHARMM) to characterize typical geometries adopted by the flanking bases in the RNA kissing-loop complexes. We focus on flanking base positions in multiple x-ray and NMR structures of HIV-1 DIS kissing complexes and kissing complex from the large ribosomal subunit of Haloarcula marismortui. An initial x-ray open conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 102 publications
5
83
0
Order By: Relevance
“…The production MD runs were carried out with constant pressure boundary conditions (relaxation time of 1.0 ps). Our methods for equilibration and production run protocols are described in greater detail elsewhere (33,74,77,78). Translational and rotational center-of-mass motions were initially removed, and periodically, simulations were interrupted to have the center-ofmass removed again by a subtraction of velocities to account for the "flying ice cube" effect (79).…”
Section: Unbiased Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The production MD runs were carried out with constant pressure boundary conditions (relaxation time of 1.0 ps). Our methods for equilibration and production run protocols are described in greater detail elsewhere (33,74,77,78). Translational and rotational center-of-mass motions were initially removed, and periodically, simulations were interrupted to have the center-ofmass removed again by a subtraction of velocities to account for the "flying ice cube" effect (79).…”
Section: Unbiased Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Similar short-comings apply to an all-atom study of the flanking bases in RNA kissing-complexes, which noted some transitions from configurations where the bulge bases are inserted into the helix to configurations where the bases are flipped out. 45 A noteworthy all-atom study of RNA molecules containing varying bulge sizes observed the presence of a wobble G-U base pair flanking the bulge that increased flexibility of the structure when compared with a Watson-Crick G-C base pair in the same location. 46 As noted earlier, the oxDNA potential cannot capture the influence of non-Watson-Crick interactions on flexibility in bulged systems.…”
Section: Comparison With Experiments and All-atom Simulationsmentioning
confidence: 99%
“…29,[40][41][42] The degree of coarse-graining in oxDNA allows us to study the equilibrium ensemble of junction configurations, which involves observing substantial structural transitions at the junction repeatedly for each system. All-atom investigations of DNA and RNA systems containing bulges [44][45][46] have not yet been performed with this scope, due to the cost of simulating allatom force fields.…”
Section: Introductionmentioning
confidence: 99%
“…49,51,[54][55][56] Other RNA kissing motifs were also studied by means of MD, including H3 stem-loop of Moloney murine leukemia virus, 46 TAR elements of HIV 31,57 and kissing complex from 23 rRNA. 58 Due to inconsistency among the previously published results for simulations of DIS kissing complexes and availability of new experimental structures we were motivated to substantially extend theoretical studies of kissing complexes. We have performed multiple simulations (close to 1 ls of total) using different starting experimental structures, different ion conditions and AMBER and CHARMM force fields.…”
mentioning
confidence: 99%